IMPLEMENTASI PEMBELAJARAN BERBASIS MULTI REPRESENTASI UNTUK PENINGKATAN PENGUASAAN KONSEP FISIKA KUANTUM - ., Abdurrahman; ., Liliasari; Rusli, A; Waldrip, Bruce (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: Implementation of Multiple-Representation-Based Instructions to Improve the Mastery of Quantum Physics Concepts. This study aimed to design and investigate the role of multiple-representation-based instructions in the improvement of student teachers’ quantum physics mastery. This study used a quasi-experimental control group pretest-posttest design as quantitative part of a mixed-methods study. The subjects were student teachers of physics in the Department of Mathematics and Science Education in a state university in Lampung Province in the 2009-2010 academic year. For assessing the quantum physics mastery, the Quantum Physics Concept Achievement Test (QPCAT) was used. The quantitative analyses were conducted using the Mann Whitney U test. The results showed that multiple-representation-based instructions had a significant effect on student teachers’ quantum physics concept mastery. The results of semi-structured interviews as qualitative part of this study indicated that in the experimental group the students used a variety of representation modes in the learning process and were capable of using the most appropriate one to solve a given quantum physics concept problem. Keywords: quantum physics, multiple representations, concept mastery